PEMBUATAN MIKROKRISTALIN SELULOSA (MCC) DARI LIMBAH PENGGERGAJIAN SERBUK KAYU JELUTUNG (DYERA sp) - Benni Iskandar (Jurnal Penelitian Farmasi Indonesia)
A study on the preparation and characterization of microcrystalline cellulose from waste of sawdust has been carried out. A portion of alpha-cellulose was yielded from multi stage pulping proces of 500 grams of sawdust and it was hydrolized using hydrochloric acid to affort microcrystalline cellulose. 72 grams of microcrystalline cellulose 14,4 % rendement was obtained as white-fine powder, odorless and tasteless. Identification test using iodinated zinc chloride solution has produced blue violet solution and its infrared spectrum gave same wavenumber as standard Avicel®. pH value this microcrystalline cellulose was 5,03 and range of its melting and boiling points were 1o. Its infrared spectrum showed the presence of OH group at 3405,47 cm-1. Based on its characterization and analysis data, this microcrystalline cellulose was an agreement with the pharmacopeia requirement. Furthermore, it’s physical and chemical properties were same as used standard Avicel®. Keywords : alpha-cellulose, avicel, infrared, microcrystalline